OCP Java SE 6 programmer practice exams (exam 310-065) - Bates, Bert ca. 20./21. Jahrhundert (Practice exams Java, 2011)
"Don't Let the Real Test Be Your First Test! Written by two of the lead developers of the Java SE Programmer Exam, OCP Java SE 6 Programmer Practice Exams is filled with more than 260 realistic practice questions to prepare you for this challenging exam. To help you understand this material, in-depth explanations of both the correct and incorrect answers are included for every question. This practical guide covers all official objectives for Exam 310-065 and is the perfect companion to SCJP Sun Certified Programmer for Java 6 Study Guide. Covers all OCP Java SE 6 Programmer exam topics, including: Declarations and Access Control Object Orientation Assignments Operators Flow Control, Exceptions, and Assertions Strings, I/O, Formatting, and Parsing Generics and Collections Inner Classes Threads Development"--Provided by publisher